Total versus partial adrenalectomy in bilateral pheochromocytoma – a systematic review and meta-analysis - Zawadzka, Karolina; Tylec, Piotr; Małczak, Piotr; Major, Piotr; Pędziwiatr, Michał; Pisarska-Adamczyk, Magdalena (Frontiers in Endocrinology, 2023)
Background In patients with bilateral pheochromocytoma, partial adrenalectomy offers the chance to preserve adrenal function and avoid the need for lifelong steroid supplementation. However, the risk of tumour recurrence raises questions about this procedure. The aim of our study was to compare partial and total adrenalectomy in bilateral pheochromocytoma through a systematic review with meta-analysis. Methods A systematic search was carried out using databases (MEDLINE, EMBASE, Scopus, Web of Science, CENTRAL) and registers of clinical trials (ClinicalTrials.gov, European Trials Register, WHO International Trials Registry Platform). This meta-analysis included studies up to July 2022 without language restrictions. A random effects model meta-analysis was performed to assess the risk of tumor recurrence, steroid dependence and morbidity in these patients. Results Twenty-five studies were included in the analysis involving 1444 patients. The relative risk (RR) of loss of adrenal hormone function during follow-up and the need for steroid therapy was 0.32 in patients after partial adrenalectomy: RR 0.32, 95% Confidence Interval (CI): 0.26-0.38, P < 0.00001, I2 = 21%. Patients undergoing partial adrenalectomy had a lower odds ratio (OR) for developing acute adrenal crisis: OR 0.3, 95% CI: 0.1-0.91, P=0.03, I2 = 0%. Partial adrenalectomy was associated with a higher risk of recurrence than total adrenalectomy: OR 3.72, 95% CI: 1.54-8.96, P=0.003, I2 = 28%. Conclusion Partial adrenalectomy for bilateral pheochromocytoma is a treatment that offers a chance of preserving adrenal hormonal function, but is associated with a higher risk of local tumor recurrence. There was no difference for the risk of metastasis and in overall mortality among the group with bilateral pheochromocytomas undergoing total or partial adrenalectomy. This study is in line with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and AMSTAR (A Measurement Tool to Assess Systematic Reviews) Guidelines (10, 11). Systematic review registration https://osf.io/zx3se.